Tsunami risk scalar determination on Northern Coastal Region of Peninsula Malaysia / Hairul Izwan Amri - Amri, Hairul Izwan (2006)
Even though the impacts of the Dec. 26th. 2004 tsunami disaster on Malaysian Coastal areas were not so damaging compared to the huge impacts on Acheh, Indonesia and other regional areas but a study need to be done so that parameters of the coastal protections namely geology, location, coastal structures and existing natural protection can be determined and recommendations can be made to the Local Authority to ensure that impacts of future strong waves in Malaysia coastal areas can be reduced to a minimum level. Regarding to the parameters, risk scalar determination can be made based on the idea to develop actual risk scalar using accurate software and certain calculation. Study case area was selected due to serious damaged and total of victims during the tsunami disaster. The idea of risk scalar development is to enhance the safety management to survive from future tsunami disaster.